Corporate environmental management and financial disclosure in Bangladesh - Amin, Md Al (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study evaluates EMA practices and proposes policies for broader adoption. Method: In January 2022, Dhaka Stock Exchange (DSE)-listed companies were methodically analyzed. 61 manufacturing companies were selected from 181 after exclusion. Interviews, structured questionnaires, and 2020–2022 corporate annual reports were used to collect data.  A multiple regression model calculated and assessed the Corporate Environmental Management Reporting Index (CEMRI), using total assets, sales, stock prices, and board size as independent variables. Results: Sector-wise analyses showed differences in EMA adoption.  In the textile industry, total sales and board size positively influence CEMRI, while stock price negatively but statistically insignificantly affects it.  Total assets are positively associated with CEMRI in the pharmaceutical industry; however, other characteristics are negatively connected. CEMRI and financial indicators were slightly correlated in food and associated industries.  Sales fell, while stock prices and assets rose in the ceramic industry.  EMA reporting was most predictable in the fuel and power sectors, where total assets, revenue, and stock prices affected CEMRI. Conclusions: This study highlights the uneven adoption of Environmental Management Accounting across manufacturing sectors in Bangladesh and underscores the need for stronger policies, regulatory frameworks, and corporate commitment to promote sustainable business practices. Limitations: The study is limited to manufacturing enterprises and a specific timeframe (2020–2022), potentially affecting generalizability.   Contribution: The findings guide policymakers and managers to strengthen sustainable corporate accountability in Bangladesh.